PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI DAN KINERJA PEGAWAI (Studi Pada Pusat Pengembangan danPemberdayaan Pendidik dan Tenaga Kependidikan/Vocational Education Development CenterMalang) - Dwiyekti Agung Nugroho (Universitas muhammadiyah malang, 2011)
ABSTRACTThis study basically aims to analyze the influence of corporate culture and transformational leadership styles onorganizational commitment and employee performance in PPPPTK/VEDC Malang. In addition, analyze organizationalcommitment mediates the influence of corporate culture and transformational leadership styles on employeeperformance. The population of this study are Civil Servants and the sample size is 78 employees. Data collectionuses the questionnaire (set of written questions addressed to the respondent) and analyses method is Path Analysis.The results show that the corporate culture significantly influences to organizational commitment, whereas transformationalleadership style does not. Corporate culture, transformational leadership style and organizational commitmentinfluence to the performance of employees. Organizational commitment may mediate the influence of corporateculture on employee’s performance, but organizational commitment is not able to mediate the influence oftransformational leadership styles to the employee performance.Keywords: corporate culture, transformational leadership, commitment, employee performance